Simulation of Performance Enhancement of Bi-Lateral Lower-Limb Amputees Through Impulse Synchronisation with Self Selected Running Step Frequency - Noroozi, Siamak; Abdul Ghaffar, Abdul Rahman; Vinney, John; Ong, Zhi Chao; Khoo, Shin Yee (2013)
Current method of enhancing the performance of a bilateral amputee runners using energy return prosthesis is rarely linked to the system dynamics. In this paper a simple simulation is used to show that if a self selected running step frequency could be synchronized with dynamic elastic response of a mass spring system extra gain in height or faster take off velocity can be achieved which results is higher state of energy equilibrium that is more favourable to running activity. Current method often relies on physiological methodology, making the differentiation between the contributions from the biological and the prosthetic element of the below-knee amputee athlete difficult. In this paper a series of mass and composite foot system are modelled based on a combination of mass, spring and damper arrangement to study the effect of gravity, mass, stiffness, damping and inertia on the dynamics characteristics of prosthesis and how human can instinctively detect the natural elastic response of such system both to cyclic excitation and impulse through self selection of frequency or impulse.It will be demonstrated that if the natural characteristics of a system are identified and synchronised with the physiological gait behaviour of a runner, performance enhancement could occur that can be stored and controlled at will by the user. In the case of a bi-lateral amputee athlete with near symmetrical gaitit can result in steady state running which can be beneficial over longer distances. Keywords: Amputee, Prosthesis, Lower-Limb, Foot, Energy